1990
DOI: 10.1111/j.1530-0277.1990.tb01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Has Direct Inhibitory Effects on Steroidogenesis in Human Granulosa Cells: Specific Inhibition of LH Action

Abstract: We have evaluated the direct effects of ethanol (EtOH) on the production of progesterone (P) and estradiol-17 beta (E2) by cultured human granulosa cells obtained during in vitro fertilization procedures. On day 3 of culture, cells were divided into control and ethanol (20 mM) groups and stimulated by hFSH (50 ng/ml), hLH (0-50 ng/ml), FSH+LH, 8 Br-cAMP (0.25 mM) and androstenedione (10(-7) M). Experiments were terminated on days 7 and 9 and DNA, P, and E2 were measured. Ethanol inhibited P and E2 secretion st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Earlier studies, with considerably lower statistical power, have demonstrated similar progesterone effects only during stimulatory conditions among premenopausal women not using oral contraceptives (Teoh et al, 1990;Saxena et al, 1990). The levels of sex hormonebinding globulin and albumin to which the major part of the sex steroids are bound were not measured in the present study, because acute changes in these proteins during alcohol intake seem unlikely during the present short time interval.…”
Section: +05%mentioning
confidence: 63%
“…Earlier studies, with considerably lower statistical power, have demonstrated similar progesterone effects only during stimulatory conditions among premenopausal women not using oral contraceptives (Teoh et al, 1990;Saxena et al, 1990). The levels of sex hormonebinding globulin and albumin to which the major part of the sex steroids are bound were not measured in the present study, because acute changes in these proteins during alcohol intake seem unlikely during the present short time interval.…”
Section: +05%mentioning
confidence: 63%
“…Long-term administration of alcohol to female rats reduces ovarian size, destroys the corpora lutea and induces changes in estrogen deficiency in the uterus and the salpinxes. There are no specific studies on the effect of ethanol on women's ovaries, even though it seems that the addition of ethanol in cultures of theca cells inhibits the progesterone and estradiol response (109).…”
Section: Systemic Diseases and Ovarian Dysfunctionmentioning
confidence: 99%
“…32 The high number of degranulated mast cells in the EtOH confirmed this process already described by Mendes et al 33 The increase of intact and degranulated mast cells observed in T could be attributed to a high expression of IL-10 in the prostate, because this cytokine is proposed to stimulate the proliferation of mast cells. 34 In addition to the indirect effects caused by ethanol (e.g., decreasing plasma testosterone and triggering hormonal imbalance) 35,36 , some authors suggest a direct action based on the hypothesis that prostate is able to metabolizes ethanol to acetaldehyde which leads to the generation of free radicals and a subsequent oxidative stress in the organ. 37,38 The increased expression of NFR2 in the EtOH group seems to agree with the authors, because this transcription factor is a powerful redox sensor activated in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 98%